Effects of Moringa oleifera Lam. and Azadirachta indica A. Juss. leaf extract in treatment of tannery effluent - Sinha, Sankar Narayan; Paul, Dipak; Biswas, Karabi (Our Nature, 2017)
The effect of leaf extracts of Moringa oleifera and Azadirachta indica using ethanol as solvent on tannery waste water treatment was investigated for a period of five days and their phytochemical constituents were analyzed. All the extracts were found to be efficient in the clarification and sedimentation of total solids in the tannery waste water sample. On the 5th day, sample treated with 10 ml of extract showed higher reduction of electrical conductivity, pH, chloride, sulfate along with dissolved oxygen. The significant reduction of these pollution indicating parameters of the tannery effluent indicated its high applicability to treat the tannery wastes along with other waste water treatment in near future. This is the first report of decontamination of tannery waste water by Azadirachta indica leaf extract. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.